Sulfate as a regulator of Bacteroides thetaiotaomicron glutamate decarboxylase: Elucidating the bipartite binding and regulation mechanism - Shujun Liu; Yulu Wang; Boting Wen; Ran Ran; Haiyan Yu; Abeer Mohamed; Xue Han; Zhen Li; Fengjiao Xin (Food Chemistry, 2026)

Isolation, screening and complete genome sequencing of cellulolytic fungi for enhanced fermentation of rice bran - Shiyi Lu; Weining Sun; Yaxuan Peng; Boting Li; Hongyan Li; Jing Wang; Baoguo Sun (Food Bioscience, 2026)

Decoding built environment impacts and regional interdependence of urban traffic emissions using interpretable deep learning - Boting Qu; Fen Li; Yuan Gao (Journal of Transport Geography, 2026)

Comprehensive investigation of the IKKα gene and TBK1 gene's identification, molecular evolution, and expression profiling in lampreys - Boting Lan; Xinyu Du; Ning Yang; Si Gao; Tiesong Li; Peng Su (Fish & Shellfish Immunology, 2026)

Construction and application of an eco-hydrological model for assessing watershed wetland water storage capacity - Boting Hu; Guangxin Zhang; Jingxuan Sun; Fengping Li; Yanfeng Wu; Liwen Chen; Qingsong Zhang (Science China Earth Sciences, 2026)

Q_EDQ: Efficient path planning in multimodal travel scenarios based on reinforcement learning - JianQiang Yan; Yinxiang Li; Yuan Gao; BoTing Qu; Jing Chen (Travel Behaviour and Society, 2025)

Porous hollow microspheres based on industrial solid waste enhance biomethane recovery from corn straw - Xiaotian Chen; Changchang Zang; Yuting Xie; Ke Wang; Yang Li; Ruifang Lv; Boting Wen; Zongjun Cui; Xufeng Yuan (Bioresource Technology, 2024)

Biomass derived hard carbon materials for sodium ion battery anodes: Exploring the influence of carbon source on structure and sodium storage performance - Boting Yan; Cheng Han; Yiming Dai; Mingyang Li; Zhaoyang Wu; Xiangpeng Gao (Fuel, 2024)

Rhizosphere shapes the associations between protistan predators and bacteria within microbiomes through the deterministic selection on bacterial communities - Yang Yue; Chen Liu; Boting Xu; Yijin Wang; Qihui Lv; Zeyuan Zhou; Rong Li; George A. Kowalchuk; Alexandre Jousset; Qirong Shen; Wu Xiong (Environmental Microbiology, 2023)
The assembly of bacterial communities in the rhizosphere is well‐documented and plays a crucial role in supporting plant performance. However, we have limited knowledge of how plant rhizosphere determines the assembly of protistan predators and whether the potential associations between protistan predators and bacterial communities shift due to rhizosphere selection. To address this, we examined bacterial and protistan taxa from 443 agricultural soil samples including bulk and rhizosphere soils. Our results presented distinct patterns of bacteria and protistan predators in rhizosphere microbiome assembly. Community assembly of protistan predators was determined by a stochastic process in the rhizosphere and the diversity of protistan predators was reduced in the rhizosphere compared to bulk soils, these may be attributed to the indirect impacts from the altered bacterial communities that showed deterministic process assembly in the rhizosphere. Interestingly, we observed that the plant rhizosphere facilitates more close interrelationships between protistan predators and bacterial communities, which might promote a healthy rhizosphere microbial community for plant growth. Overall, our findings indicate that the potential predator–prey relationships within the microbiome, mediated by plant rhizosphere, might contribute to plant performance in agricultural ecosystems.

Population pharmacokinetics of unbound valproic acid in pediatric epilepsy patients in China: a protein binding model - Xurui Gu; Min Zhu; Changcheng Sheng; Shuran Yu; Qilin Peng; Mubai Ma; Yani Hu; Ziran Li; Zheng Jiao; Boting Zhou (European Journal of Clinical Pharmacology, 2021)

Changes in Small Intestine Tissue Compressed by a Linear Stapler Based on Cole Y Model - Yu Zhou; Binbin Ren; Boting Li; Jingjing Xu; Yiyun Jin; Chengli Song (Annals of Biomedical Engineering, 2016)